Searching for hidden activities: Percussive tools from the Oldowan and Acheulean of West Turkana, Kenya (2.3–1.76 Ma) - (:unkn) unknown (My University, 2020)
Over the last thirty years, investigations in the Nachukui Formation (West Turkana, Kenya) have revealed theimportance of the region for human evolution studies within an archaeological sequence spanning the period 3.3million years (Ma) to 0.7 Ma. Despite the numerous sites discovered, little is known about pounding activitiesduring this time period in the region. In this paper, we present an analysis of percussive tools from three WestTurkana archaeological sites: Lokalalei 2C, Kokiselei 1 and Kokiselei 4, dated between 2.3 Ma and 1.76 Ma. Theirchronological range allows us to conduct a diachronic comparison of the percussive activities during a time spanwith two hominin genera (Australopithecus boisei, early Homo and Homo erectus). The three assemblages arecompared with others from the Early Stone Age and with experimental percussive tools. Despite the stablepredominance of hammerstones associated with stone knapping activities over time in the Nachukui Formation,our macro- and microscopic analyses reveal an inter-site variability in the type and re-use of percussive tools forspecific heavy-duty pounding activities. When compared with other Early Stone Age sites, Lokalalei 2C, Kokiselei1 and Kokiselei 4 similarly present a low frequency of pounding tools but a high number of blanks used for bothflaking and pounding activities, suggesting that the reutilization of the tools and the change in their functionalitywas common in the ESA lithic record.
Keywords: African Research